2009
DOI: 10.1111/j.1540-8175.2009.00960.x
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Apical Thin Point Viewed with Two‐Dimensional Echocardiography

Abstract: The aim of this study was to evaluate the usefulness of two-dimensional echocardiography in observing the left ventricular apical thin point (LVATP) and to view the change in thickness and width of the LVATP during the cardiac cycle. Transthoracic echocardiography was performed in 32 healthy adult volunteers to observe the LVATP in an apical three-chamber view. The width and thickness of the LVATP were measured at the end-diastole as well as at the end-systole. With two-dimensional echocardiography, the LVATP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 3 publications
(3 reference statements)
1
10
0
Order By: Relevance
“…Hence various studies may differ on the localization of its territory. Forth, as noted by Baosheng et al, 3 the width of the LVATP varies across the cardiac cycle. These may lead to different measurements if these measurements were taken at different phases of the cardiac cycle.…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…Hence various studies may differ on the localization of its territory. Forth, as noted by Baosheng et al, 3 the width of the LVATP varies across the cardiac cycle. These may lead to different measurements if these measurements were taken at different phases of the cardiac cycle.…”
mentioning
confidence: 80%
“…Multiple studies are reported on the left ventricular apex, as it contains, at its very tip, a thin‐point. Some authors have described it as the “left ventricular apical thin‐point” (LVATP) 1–4 . In 1977, Bradfield et al 1 provided the earliest documented confirmation of the apical thin‐point, measured at necropsy the apical thin‐point and found it to be ≤1 mm in 67% of examined hearts and ≤2 mm in 97% of examined hearts.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Thinning of the myocardium associated with a segmental wall motion abnormality suggests an area of infarction or scarring. However, focal wall thinning at the ventricular apex can be seen in normal populations that have normal cardiac function without symptoms or a previous history of a myocardial infarction [24][25][26] (Fig. 13).…”
Section: Left Ventricular Apical Thinningmentioning
confidence: 95%